Muhammadiyah Dan Tantangan Pornografi: Membentuk Generasi Berakhlak Di Era Digital - Zuhri; Muhammad Rizki Setyawan; Oman Fathurohman SW (Al-Mau’izhoh: Jurnal Pendidikan Agama Islam, 2025)
The rapid development of digital technology has reshaped social behavior among Indonesian youth, who constitute the most active internet users and are increasingly exposed to various online risks, including digital pornography. This phenomenon is no longer limited to explicit adult platforms but extends to algorithm-driven social media content, short videos, pop-up advertisements, and AI-generated deepfake materials that are widely accessible through smartphones. Empirical studies show that repeated exposure to pornography can disrupt the brain’s reward system, increase impulsivity, distort perceptions of sexuality, and contribute to addiction patterns, thereby affecting emotional regulation, social behavior, and academic performance. From an Islamic ethical perspective, pornography is classified as fahisyah that violates moral integrity, undermines ḥayā’, and threatens the preservation of intellect and personal honor. Muhammadiyah reinforces this stance through official fatwas and digital ethics guidelines outlined in the Pedoman Hidup Islami Warga Muhammadiyah (PHIWM), emphasizing the obligation to prevent moral harm and promote responsible media engagement. As a major Islamic organization with extensive educational institutions, Muhammadiyah plays a strategic role in guiding adolescents amid digital challenges. This study employs a qualitative library research method supported by content analysis to explore the issue of pornography through Islamic moral teachings, Muhammadiyah’s normative framework, and contemporary scientific findings. The analysis highlights the multidimensional risks of pornography and underscores the need for integrated preventive strategies involving families, schools, religious institutions, and digital literacy programs. The study concludes that strengthening moral resilience and digital ethics is essential for protecting youth in an increasingly technology-driven environment.